Legalitas Drone (Pesawat Tanpa Awak) Sebagai Alat Melakukan Mata-Mata Dalam Perang - Harling, Firstjuan Imanuel Van; Peilouw, Johanis Steny Franco; Hanafi, Irma Halimah (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The use of drone technology as a weapon of war raises several problems, both in terms of action and consequences. In terms of action, when drones are used as weapons, participants in armed conflict are no longer just humans fighting each other, but between (non-living) robots against living (humans). Apart from the legality of war and the use of drones as weapons of war, drone attacks can be carried out secretly, at any time and without the knowledge of the enemy.Purposes of the Research: This writing aims to examine and find out the use of drones (unmanned aircraft) as a tool for espionage in International Humanitarian Law and more specific rules regarding the use of drones (unmanned aircraft) as a tool for spying in war.Methods of the Research: The type of research used in this paper is normative legal research. As for answering the problems in this study, the authors use three approaches to the problem, namely the statutory approach (statute approach), conceptual approach (conceptual approach) and case approach (case approach). The procedure for collecting legal materials carried out by the author is by searching for and collecting laws and regulations related to the legal issues at hand. Legislation in this case includes both legislation and regulation. Analysis of legal material uses qualitative methods, namely studies related to legal norms contained in international law legislation and legal norms that exist in society.Results of the Research: The results of this study indicate that the use of drones (unmanned aircraft) as a tool to carry out espionage in International Humanitarian Law, is contained in Article 36 of Additional Protocol I to the 1977 Geneva Convention. Article 36 intends to maintain the development of weapons used both by countries and international organizations to continue to respect, maintain and not cross the boundaries of existing international humanitarian law principles. The current arrangement is too old and cannot be definitively binding. The use of drones as weapons has been carried out in the absence of an adequate legal regulation on this matter, Article 36 of Additional Protocol I of 1977 only contains general matters regarding the development of weapons technology and methods of warfare, but does not specifically and specifically regulate the use of drones. The absence of legal rules that specifically and specifically regulate the use of drones, which relate to their use as weapons, this will open up enormous opportunities for misuse and violations of international humanitarian law.